Literature Review Efektivitas Latihan Aerobik Dalam Meningkatkan Fungsi Motorik Pada Lansia Dengan Penyakit Parkinson - Linlin Lindayani; Dewi Marfuah; Diwa Agus Sudrajat; Eva Supriatin (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Parkinson's disease is a neurodegenerative disease caused by a decrease in the amount of dopamine in the brain that plays a role in controlling movement due to damage to nerve cells in the Substantia Nigra Pars compacta (SNc) in the brain stem and abnormal protein aggregation in the form of Lewy bodies, which contain -synuclein. Parkinson's disease is characterized by the presence of dominant motor symptoms in the form of tremor at rest, rigidity, bradykinesia, and loss of postural reflexes. Physical rehabilitation can generally be used in patients with Parkinson's disease to improve health and relieve symptoms. Aerobic exercise is believed to promote fitness in Parkinson's patients and improve motor function in the elderly with Parkinson's disease. The purpose of this literature review is to determine the effectiveness of providing aerobic exercise in improving motor function in the elderly with Parkinson's disease. The implementation strategy uses a literature review technique obtained through an online search process on related research journals that have existed previously. The search was carried out through the PubMed database. Giving aerobic exercise is effective in improving motor function in the elderly with Parkinson's disease.